Pengolahan Air Limbah Domestik Menggunakan Teknologi Biofilm dengan Media Potongan Bambu untuk Penurunan Kadar Deterjen, COD, BOD, dan Amonia - Saddam Husein (FT-USNI, 2019)
ncreasing the amount of domestic waste water which is not balanced by the increase in receiving water bodies both in terms of capacity and quality, causes the amount of waste water entering the water body to exceed the carrying capacity and carrying capacity. Then domestic wastewater in the residential environment for the future has the potential to become a fairly serious threat to pollution of the aquatic environment. Based on the results of the study it was found that the percentage of pollutant levels decreased against expotentially tested parameters with the incubation period. The greatest effectiveness occurred at the incubation time on the second day, decreasing detergent content from 34.88 mg / L to 8.10 mg / L with the reactor effectiveness value of 76.78%. COD levels decreased from 310.77 mg / L to 60.37 mg / L with a reactor effectiveness value of 80.57%. BOD levels decreased from 282.55 mg / L to 50.32 mg / L with a reactor effectiveness value of 82.19% and a decrease in ammonia content from 157.77 mg / L which was 53.81 mg / L with a reactor effectiveness value of 65.89%.